PERAN GURU DALAM MENINGKATKAN PERILAKU ISLAMI SISWA SMA N 2 OKU - Dewa Ikhram; Muhammad Win Afgani; Fajri Ismail (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Education is so very important to change human morals, especially the many moral declines committed by children and adolescents. In this case, it is a tough task for the three education centers, both in the family, school and community. These three educational institutions should work together to achieve Islamic educational goals.